Pengaruh Media Sosial, Harga Dan Lifestyle Terhadap Keputusan Pembelian Produk Fast Fashion - Resnawanti; Nofri Yendra (CV. Akira Java Bulu, 2025)
This research aims to determine the influence of social media, price and lifestyle on purchasing decisions for fast fashion products, a case study of students majoring in management at Dharma Andalas University. The population in this study was students majoring in management at Dharma Andalas University, totaling 518 people by collecting samples using the sample size calculator feature via the website www.raosoft.com so that the sample was 110 people. Data was obtained by distributing questionnaires and then processed and tested using SPSS (Statistical Product and Service Solutions) v21. From the research conducted, it is known that based on the results of hypothesis testing, it shows 1). Media has a positive and significant influence on purchasing decisions, 2). Price has a positive and significant effect on purchasing decisions, 3). Lifestyle has a positive and significant effect on purchasing decisions, 4). Social media, price and lifestyle have a positive and significant influence on purchasing decisions. Furthermore, the purchasing decision variable (Y) is influenced by social media, price and lifestyle at 68.5%, while the remaining 31.5% is influenced by other variables that are not in this research.